2021
DOI: 10.24167/celt.v20i1.2445
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Perception and Vision about TPACK and Its Implementation

Abstract: The need for educators to integrate the use of technology in the classroom is growing for the past few years. However, previous studies indicated that the use of Information and Communications Technology (ICT) is still at a low level of what the education program requires. Furthermore, it seems that in the field of language education, there is limited research focusing on pre service teachers (PTs). Therefore, to address this gap, this paper aims at investigating how the pre service teacher's understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The questionnaire results showed that the lecturers' literacy levels on technology, pedagogy, content knowledge, and TPACK are on a moderate stage. Next, Ringotama [27] investigates how the pre-service teachers understand the TPACK principle and apply TPACK in their classrooms. Then, Alnujaidi [6] investigates the level of knowledge of pre-service and in-service EFL teachers in Saudi Arabia related to material content, pedagogy, and technology, concerning gender, school ability in internet access, and training in using technology.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%
“…The questionnaire results showed that the lecturers' literacy levels on technology, pedagogy, content knowledge, and TPACK are on a moderate stage. Next, Ringotama [27] investigates how the pre-service teachers understand the TPACK principle and apply TPACK in their classrooms. Then, Alnujaidi [6] investigates the level of knowledge of pre-service and in-service EFL teachers in Saudi Arabia related to material content, pedagogy, and technology, concerning gender, school ability in internet access, and training in using technology.…”
Section: Issn: 2252-8822 mentioning
confidence: 99%